2020
DOI: 10.1182/blood.2020007092
|View full text |Cite
|
Sign up to set email alerts
|

CANOMAD: a neurological monoclonal gammopathy of clinical significance that benefits from B-cell–targeted therapies

Abstract: CANOMAD (chronic ataxic neuropathy, ophthalmoplegia, IgM paraprotein, cold agglutinins and disialosyl antibodies) is a rare syndrome characterized by chronic neuropathy with sensory ataxia, ocular and/or bulbar motor weakness, in the presence of a monoclonal IgM reacting against gangliosides containing disialosyl epitopes. Data regarding associated hematologic malignancies and effective therapies in CANOMAD are scarce. We conducted a French multicenter retrospective study that included 45 patients with serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 40 publications
6
66
1
1
Order By: Relevance
“…However, a rigid interpretation of this pathway would only result in testing for ganglioside antibodies alongside anti-MAG antibodies in patients demonstrating conduction slowing/demyelination on electrophysiological testing. Findings from a recent large study of 45 patients with CANOMAD revealed a demyelinating pattern in 60%, with predominantly axonal features in 27% [3].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, a rigid interpretation of this pathway would only result in testing for ganglioside antibodies alongside anti-MAG antibodies in patients demonstrating conduction slowing/demyelination on electrophysiological testing. Findings from a recent large study of 45 patients with CANOMAD revealed a demyelinating pattern in 60%, with predominantly axonal features in 27% [3].…”
Section: Discussionmentioning
confidence: 95%
“…Ataxic neuropathy is frequently the dominant symptom, potentially causing severe disability. Disease trajectory is variable, typically extending over decades, with progression in two‐thirds and a third relapsing‐remitting [ 3 ]. Misdiagnosis is common, in part because fewer than half of the patients exhibit the full spectrum of clinical features, ultimately delaying appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IgM disialosyl antibodies could be associated with CANOMAD: Chronic Ataxic Neuropathy with Ophthalmoplegia, M-protein, cold Agglutinins and Disialosyl ganglioside (IgM Anti-GD1b/ GT1b/GQ1b) antibodies. 32 In CANOMAD, nerve conduction tests show a mixed pattern of axonal loss and demyelinating features. 30-40% of IgM-related demyelinating neuropathies have no identifiable antibodies.…”
Section: Polyneuropathymentioning
confidence: 99%